2013
DOI: 10.1016/j.intell.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The structure of working memory and how it relates to intelligence in children

Abstract: This study explored the structure of working memory, and its relationship with intelligence in 176 typically-developing children in the 4 th and 5 th grades at school. Different measures of working memory (WM), and intelligence (g) were administered. Confirmatory factor analyses showed that WM involves an attentional control system and storage aspects that rely on domain-specific verbal (STM-V) and visuospatial (STM-VS) resources. The structural equation models showed that WM predicts a large portion (66%) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 55 publications
6
55
0
2
Order By: Relevance
“…Last, while in the Corsi task the sequences are only presented once or twice and upon making a mistake, the participant is not allowed to try the longer sequences, in our memory task, all sequence lengths are presented multiple times and all participants are presented with all 36 trials. This method of administering the task has been used before (Giofrè et al, 2013;Hornung et al, 2011) and enables a more detailed estimate of the memory performance than measuring the span level reached. This estimate was obtained by determining the fraction of recall, which was the fraction of correctly reproduced cued locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Last, while in the Corsi task the sequences are only presented once or twice and upon making a mistake, the participant is not allowed to try the longer sequences, in our memory task, all sequence lengths are presented multiple times and all participants are presented with all 36 trials. This method of administering the task has been used before (Giofrè et al, 2013;Hornung et al, 2011) and enables a more detailed estimate of the memory performance than measuring the span level reached. This estimate was obtained by determining the fraction of recall, which was the fraction of correctly reproduced cued locations.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless a description of the correlation between these tasks for the full adolescence period has, to our knowledge, not been published. Previous studies into this correlation have focused on adult populations (Miyake et al, 2001) and small children (Giofrè, Mammarella, & Cornoldi, 2013). Finally, measures for memory capacity are usually rather coarse.…”
Section: Introductionmentioning
confidence: 99%
“…An abundant body of research has shown that processing speed (Coyle, 2013;Jensen, 1998) and WM (Cornoldi, Orsini, Cianci, Giofrè, & Pezzuti, 2013;Demetriou et al, 2013;Giofrè, Mammarella, & Cornoldi, 2013) are involved in intellectual functioning. The present evidence confirms that this relationship may differ, however, in particular groups -as already suggested in the case of children with ADHD, who may struggle with WM tasks despite a high level of intelligence (Cornoldi, Giofrè, Calgaro, & Stupiggia, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There is ample research to show that fluid intelligence and WM are substantially related in both adults (e.g., Ackerman et al, 2005;Conway et al, 2011) and children (e.g., Engel de Abreu, Conway, & Gathercole, 2010;Giofrè, Mammarella, & Cornoldi, 2013;Hornung, Brunner, Reuter, & Martin, 2011). There is much less empirical research addressing the relationship between sustained attention and intelligence as well as the relationship between sustained attention and WM.…”
Section: Relationship Between the Constructsmentioning
confidence: 99%